Loss of mitochondrial protease ClpP protects mice from diet‐induced obesity and insulin resistance. (2nd February 2018) - Bhaskaran, Shylesh; Pharaoh, Gavin; Ranjit, Rojina; Murphy, Ashley; Matsuzaki, Satoshi; Nair, Binoj C; Forbes, Brittany; Gispert, Suzana; Auburger, Georg; Humphries, Kenneth M; Kinter, Michael; Griffin, Timothy M; et al.
Abstract: Caseinolytic peptidase P (ClpP) is a mammalian quality control protease that is proposed to play an important role in the initiation of the mitochondrial unfolded protein response (UPR mt ), a retrograde signaling response that helps to maintain mitochondrial protein homeostasis. Mitochondrial dysfunction is associated with the development of metabolic disorders, and to understand the effect of a defective UPR mt on metabolism, ClpP knockout ( ClpP −/− ) mice were analyzed. ClpP −/− mice fed ad libitum have reduced adiposity and paradoxically improved insulin sensitivity. Absence of ClpP increased whole‐body energy expenditure and markers of mitochondrial biogenesis are selectively up‐regulated in the white adipose tissue (WAT) of ClpP −/− mice. When challenged with a metabolic stress such as high‐fat diet, despite similar caloric intake, ClpP −/− mice are protected from diet‐induced obesity, glucose intolerance, insulin resistance, and hepatic steatosis. Our results show that absence of ClpP triggers compensatory responses in mice and suggest that ClpP might be dispensable for mammalian UPR mt initiation. Thus, we made an unexpected finding that deficiency of ClpP in mice is metabolically beneficial. Synopsis: Mitochondrial matrix protease ClpP is proposed to play an important role in the initiation of mammalian mitochondrial unfolded protein response (UPR mt ). This study reveals that ClpP deficiency in mice has paradoxical beneficial effects on metabolism and ClpP might be dispensable for mammalian UPR mt initiation. ClpP −/− mice have reduced adiposity and improved insulin sensitivity. Mitochondrial biogenesis markers and respiration are selectively up‐regulated in white adipose tissue of ClpP −/− mice. ClpP −/− mice are protected from diet‐induced obesity, glucose intolerance, and insulin resistance. Abstract : Mitochondrial matrix protease ClpP is proposed to play an important role in the initiation of mammalian mitochondrial unfolded protein response (UPR mt ). This study reveals that ClpP deficiency in mice has paradoxical beneficial effects on metabolism and ClpP might be dispensable for mammalian UPR mt initiation.